Using a Multi Omic Approach to Investigate a Diet Intervention in Young Adults at Risk of Disease - Saule Kassymbekova; Joy Pepania; Masooma Al Balushi (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: To examine the impact of an 8-week dietary intervention, based on USDA 2010 guidelines, on nutritional behaviors, metabolome, and microbiome of young adults at risk of disease. Methodology: This study utilized an 8-week, free-living, randomized trial using Nutritionist Pro™ (Axxya Systems), ActiGraph GT3X accelerometers, and 16S rRNA sequencing for microbial profiling. Participants were counseled with weekly tailored interventions by a Registered Dietitian Nutritionist (RDN). Biochemical, anthropometric, dietary intake, and microbiome data were collected and analyzed using SAS and JMP software. Main Findings: The intervention increased fruit, vegetable, and fiber intake while reducing saturated fat and empty calorie consumption. Significant improvements were observed in systolic blood pressure, waist circumference, and total cholesterol. Microbial analysis revealed decreased Firmicutes and increased Bacteroidetes post-intervention, along with improved inflammatory markers and serum ceramide levels. Novelty/Originality of this study: This study uniquely integrates dietary intervention with a multi-omic approach including metabolomics and microbiome analysis in a young adult population. It provides foundational evidence for personalized nutrition and translational research, highlighting how targeted dietary changes can influence microbial composition and metabolic health.